Predation and nest success of forest birds in native and non-native habitat on Saipan, Mariana Islands - Sachtleben, Thalia, author; Savidge, Julie A., advisor (Colorado State University. Libraries, 2005)
The primary causes of extinctions and declines of birds on islands are predation by non-native mammals (e.g., rats and feral cats) and the removal or alteration of indigenous forests. The impact of various exotic predators and extreme modification and removal of native forest on Saipan on the nesting success of the native avifauna had not been examined. Thus, I undertook this research on the island of Saipan in 2003 and 2004 to: (i) quantify nest densities in native and non-native forest, (ii) assess nest survival and predation rates on nests in native and non-native forest, (iii) determine whether certain nest site characteristics made nests more vulnerable to predators, and (iv) identify predators of nests of target bird species. My target species were the Nightingale Reedwarbler (Acrocephalus luscinia; federally listed as endangered) and three of the more common forest species, the Golden White-eye (Cleptomis marchei), Bridled White-eye (Zosterops conspicillatus saypani) and Rufous Fantail (Rhipidura rufifrons saipanensis). The Golden White-eye is an endemic species, while the latter two are endemic subspecies. Nest densities were influenced by forest type in 2003, and by avian species, forest type, and sampling period in 2004. Daily nest survival rates varied by nest stage and species. For Bridled White-eye , daily survival rates differed by year, whereas daily survival rates were constant across years for Golden White-eyes and Rufous Fantails. In 2003, daily nest survival in all stages for Bridled White-eyes was similar to that of Golden White-eyes and Rufous Fantails. Survival estimates were higher for Golden White-eyes and Rufous Fantails than for Bridled White-eyes in the incubation and nestling stages in 2004. All predators identified by camera were avian, predominantly Micronesian Starlings (Aplonis opaca) and Collared Kingfishers (Halcyon chloris). Results from modeling the effect of nest site characteristics on daily nest survival rates were ambiguous, with much model selection uncertainty. However, there was weak evidence that higher numbers of nest support branches increased survival of Golden White-eye nests, while lower nest concealment (side cover) improved Bridled White-eye nest survival. These results were contrary to my predictions. No nest site variables that I measured appeared to affect Rufous Fantail daily nest survival rates. Although not a target species of this study, I incidentally found the first nests of the Micronesian Honeyeater (Myzomela saffordi rubratra) on Saipan. I report my descriptions of the nests, nestlings, and parental behavior in Chapter 2. Measured nests (n = 3) averaged 46.7 mm in cup diameter, 65.7 mm in outer diameter, 41.3 mm in cup height, and 55.3 mm in external nest height. Nesting materials were primarily vine tendrils and what appeared to be Casuarina equisetifolia needles. Nests, nest placement and adult bird behavior appeared similar to those reported for this species prior to its extirpation on Guam.
Covers not scanned.
Keywords: Forest birds -- Northern Mariana Islands -- Saipan (Northern Mariana Islands); Forest birds -- Effect of predation on